Math, asked by krishan427384kk, 1 year ago

please please solve it​

Attachments:

Answers

Answered by ankitsaini76216
2

Answer:

c^2=a^2(1+m^2)

Step-by-step explanation:

दी  \: गई   \: समीकरण \\ (1 +  {m}^{2} ) {x}^{2}  + 2mcx + ( {c}^{2}-  {a}^{2} ) = 0 .....(1) \\  \\ समीकरण  (1)\: की   \: तुलना a {x}^{2}  + bx + c = 0  \: से \:  करने \:  पर \\  \\ a = (1 +  {m}^{2} ) \:  ,b = 2mc \: ,  c =  {c}^{2}  -  {a}^{2}  \\ अत: \:    विविक्तकर \\  {b }^{2}  - 4ac = 0 \\ (2mc) ^{2}  - 4 \times (1 +  {m}^{2} )( {c}^{2}  -  {a}^{2} ) = 0 \\ 4 {m}^{2}  {c}^{2}  - 4(1 +  {m}^{2} )( {c}^{2}  -  {a}^{2} ) = 0 \\ 4( {m}^{2}  {c}^{2}  - (1 +  {m}^{2} )( {c}^{2}  -  {a}^{2} ) = 0 \\  {m}^{2}  {c}^{2}  = (1 +  {m}^{2} )( {c}^{2}  -  {a}^{2} ) \\  =        {c}^{2}  +  {m}^{2}  {c}^{2}  -  {a}^{2}  -  {a}^{2}  {m}^{2}  \\      {c}^{2}  =  {a}^{2} (1 +  {m}^{2} )

I hope this help you

Similar questions